Facile synthesis of monodisperse ZnS capped CdS nanocrystals exhibiting efficient blue emission - Reiss Peter; Protière Myriam (Nanoscale Research Letters, 2006)
Abstract A new method for the capping of colloidal CdS nanocrystals with ZnS shells is presented. A combination of the monomolecular precursor zinc ethylxanthate (Zn(ex)2) and zinc stearate was used to replace hazardous organometallic reagents usually applied in this procedure, i.e. bis(trimethylsilyl) sulfide and diethylzinc. Its simple preparation, air-stability and low decomposition temperature of 150 °C make Zn(ex)2a very suitable source for the ZnS shell growth. With this precursor, highly luminescent CdS/ZnS core/shell nanocrystals (Q.Y. 35–45%), exhibiting narrow emission linewidths of 15–18 nm (FWHM) in the blue spectral region, can reproducibly be obtained.